Development Flipbook Reading Explanatory Texts with the DRTA Model - Annisa Rahma Anggraeni; Memet Sudaryanto; Etin Pujihastuti (Publikasi Pendidikan, 2024)
This research develops an electronic module through a flipbook on explanation text for class VIII SMP/MTs with the DRTA learning model. The research background is the need for interactive learning resources to help students understand explanatory texts. This study uses research and development model analysis, design, development, implementation, and evaluation (ADDIE) with a mixed analysis technique. The results of this research are (1) the development of the Flipbook is analysis, design, and development through Flip PDF Professional and validation, implementation, and evaluation; (2) the outcomes using the Flipbook reach the KKM limit of 78, the product can be used in learning.